Convergence of Baum–Katz series for sums whose terms are elements of linear m th order autoregressive sequence - Ilienko, M.; Polishchuk, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 519.21 We establish necessary and sufficient conditions for the convergence of the Baum–Katz series for the sums of elements of linear mth order autoregressive sequences of random variables.